Tungiasis: Case Report of a Traveller to Kenya - Scalvenzi, Massimiliano (S. Karger AG, 2009)
Tungiasis is a neglected parasitic skin disease caused by the permanent penetration of the female sand flea Tunga penetrans (also called jigger flea) into the skin of its host. Growing urbanisation, improved housing and the use of appropriate footwear have presumably led to an overall reduction of the occurrence of this ectoparasitosis within the last few decades. However, it is still highly prevalent in regions where people live in extreme poverty, such as in many Latin American and African countries [1, 2]. We report the case of a 44-year-old woman who returned from an excursion trip to Kenya's savannah with an infection of T. penetrans located on her right big toe around the nail. The natural history, pathology, epidemiology, diagnosis, therapy and control of this parasitic skin disease are discussed [1].